Performance of a Maternal Abdominal Surface Electrode System for Fetal Heart Rate and Uterine Contraction Monitoring from 34 to 37 Weeks - Gonzalez, Maritza; Hill, Meghan; Cohen, Wayne R. (American Journal of Perinatology, 2021)
Objective The objective of this study was to compare performance of a maternal surface electrode patch with ultrasound- and tocodynamometer-based monitoring to detect fetal heart rate and uterine contractility in late preterm labors.Study Design Thirty women between 340/7 and 366/7 weeks' gestation were monitored simultaneously with a Doppler/tocodynamometer system and a wireless fetal–maternal abdominal surface electrode system. Fetal and maternal heart rate and uterine contraction data from both systems were compared. Reliability was measured by the success rate and percent agreement. Deming regression and Bland–Altman analysis estimated the concordance between the systems. Uterine contractions were assessed by visual interpretation of monitor tracings.Results The success rate for the surface electrode system was 89.5% (95% confidence interval [CI], 85.7–93.3), and for ultrasound it was 88.4% (95% CI, 84.9–91.9; p = 0.73), with a percent agreement of 88.1% (95% CI, 84.2–92.8). Results were uninfluenced by the patients' body mass. The mean Deming slope was 1 and the y-intercept was −3.0 beats per minute (bpm). Bland–Altman plots also showed a close relationship between the methods, with limits of agreement less than 10 bpm. The percent agreement for maternal heart rate was 98.2% (95% CI, 97.4–98.8), and for uterine contraction detection it was 89.5% (95% CI, 85.5–93.4).Conclusion Fetal heart rate and uterine contraction monitoring at 340/7 to 366/7 weeks using abdominal surface electrodes was not inferior to Doppler ultrasound/tocodynamometry for fetal–maternal assessment.Registration clinicaltrials.gov/February 20, 2017/identifier NCT03057275.Key Points
Keywords: fetal heart rate monitoring; fetal ECG; abdominal fetal ECG; preterm labor; uterine contractility